PERAN METODE UNTUK MENCAPAI TUJUAN PEMBELAJARAN - H. Samiudin H. Samiudin (Universitas Yudharta Pasuruan, 2017)
Teaching methods is the way used by teachers unruk deliver lessons to students. Therefore, teachers in selecting teaching methods should be appropriate to the goals and objectives that have been set. Selection of this method is very influential on the results to be obtained. In essence, an attempt to teach teachers to create learning situations, the method used by the teacher is expected to grow a variety of learning activities for students in relation to teaching teachers. With other meanings, the learning process is a process of educational interaction between teachers who create an atmosphere of learning and learners respond to the teachers' efforts. Therefore, good teaching method is a method that can foster learning activities for students, teachers and effort in selecting a good method is an effort to take into high quality of teaching or education under his responsibility.